DINAMIKA PLIVAČKIH REZULTATA U CRNOJ GORI U PERIODU 1997-2004 GODINE - Branislav Radulović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
Social environment imposes parameters, later excepted as strict criteria, in swimming. These parameters are expresses in specific time for a specific swimming discipline. It means that the success in swimming is measured with time results. Proper measure for comparison of different swimming results is based on the best world results comparative tables. The most used tables today are LEN (at European level) and FINA (at world level). These are applied at official competitions of highest rang. However, having in mind nature of his work, the author decided to use British point tables. British point tables, full of additional parameters, give more objective and more precise differences between achieved results. The author's work comprises the best swimming achievements for each year with regard to different age groups. Each result was placed into a specially designed program and ascribed to corresponding age, sex and discipline. Consequently, he got the graphic chart showing the dynamics of the best results` development in Montenegro. They were compared according to set criteria as well as to global trends. The outcomes of the research are following conclusions: the results are getting worse with time, there are huge oscillations within the same age groups and, according to the global analyses, the best results are products of few swimmers. All this leads to the conclusion that it is absolutely necessary to work toward enlargement of the swimming potential.